A systematic review of cross-country data initiatives on agricultural public expenditures in developing countries - Anson, Richard; Mogues, Tewodaj (International Food Policy Research Institute, 2016)
This study reviews all of the relevant data and analytical initiatives or activities that focus on or include agricultural public expenditure (AgPE) in developing and transitioning countries. In addition to taking stock of such initiatives, we carry out a comparison of relevant features, describe differences and similarities, and identify possible avenues for greater collaboration and complementarity, including the use of selected empirical examples arising from the comparative review.